Anatomy of electric vehicle fast charging: Peak shaving through a battery energy storage—A case study from Oslo - Antti Rautiainen; Kalle Rauma; Lena Rohde; Antti Supponen; Fabian Raulf; Christian Rehtanz; Pertti Järventausta (IET Electrical Systems in Transportation)
Abstract The number of electric vehicle (EV) users is strongly increasing so that today roughly every second registered vehicle in Norway is an EV. To increase the EV utilization, politics, industry and the EV users strongly promote the integration of fast charging infrastructure. While the future demand of fast charging sites is a well‐studied topic, not much is known about the utilization of the existing charging sites and daily load curves. To fill this knowledge gap, usage data of a charging site in Oslo is analysed. Further on, the impact of a battery energy storage (BES) as well as a photovoltaic generator on peak load reduction is studied. The analysis shows variations and trends in the daily and weekly charging behaviour depending on the degree of utilization of the charging station. On average, a single EV user charges around 10 kWh in 19 min. Furthermore, the evidence indicates that EV users may have adapted fast charging as a part of their daily travels and it is not used only during long distance journeys. The results suggest that a BES can reduce the peak load by up to 55%. By adding a photovoltaic generator, a minor additional reduction of peak load is seen.